Assembling realities, assembling capacities: Young people and drug consumption in Australian drug education - Farrugia, Adrian Christopher (Curtin University, 2016)
This thesis analyses the constitution of young people and drug consumption in Australian drug education and social marketing texts. Drawing on the work of Gilles Deleuze and on science and technology studies, it assesses the realities assembled in these materials. Structured to reflect the assemblage approach it adopts, it argues that drug education’s articulation of rationality, sociality, space and gender, is more likely to produce than to reduce the harms traditionally thought of as “drug-related”.